International labor standards and the political economy of child labor regulation - Matthias Doepke; Fabrizio Zilibotti (Institute for the Study of Labor (IZA), 2008)
Child labor is a persistent phenomenon in many developing countries. In recent years, support has been growing among rich-country governments and consumer groups for the use of trade policies, such as product boycotts and the imposition of international labor standards, to reduce child labor in poor countries. In this paper, we discuss research on the long-run implications of such policies. In particular, we demonstrate that such measures may have the unintended side effect of lowering domestic support for banning child labor within developing countries, and thus may contribute to the persistence of the child-labor problem.
urn:nbn:de:101:1-2008111442
Keywords: J20; 330; Child labor; political economy; international labor standards; trade sanctions; Kinderarbeit; Internationale Sozialstandards; Sanktion; Jugendarbeitsschutz; Public Choice; Theorie; Entwicklungsländer